2018
DOI: 10.3139/105.110345
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Exploration of Evolutionary Structural Materials

Abstract: Abstract/KurzfassungWhile experimental high-throughput and computational methods exist for the development of functional materials, structural materials are still being developed on the base of experience, stepwise prediction and punctual support of computational models. As a result, many major breakthroughs have been and still are achieved by coincidence under non-intuitive conditions. Experimental high throughput methods allow to explore large process windows where no prediction is possible due to lack of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…For the establishment of a novel development process of new structural materials within the Collaborative Research Center "Farbige Zustände" (CRC 1232), micro samples are used for a costand resource-efficient material variation [15,16]. The mass of a conventional flat tensile specimen (5.37 g) is equal to the mass of 1315 spherical micro samples ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…For the establishment of a novel development process of new structural materials within the Collaborative Research Center "Farbige Zustände" (CRC 1232), micro samples are used for a costand resource-efficient material variation [15,16]. The mass of a conventional flat tensile specimen (5.37 g) is equal to the mass of 1315 spherical micro samples ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of technological development requires a constant search for new materials with defined properties. In order to accelerate ample and expansive studies of various metal compositions and structuring treatments, a highthroughput investigation of spherical micro samples is currently considered [1]. The investigation of micro samples results in descriptors, which are connected with the mechanical properties of the macro materials [2].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the obtained microstructure states and associated micro-properties are characterized, up-scaled to macro level and valued. By means of machine learning and heuristic methods, the experimental plans are refined and the experimental procedure is continued until, finally, a novel material with the desired properties is found [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies regarding DSC measurements on steels can be found in the literature, e.g., concerning the determination of martensite decay [4]. In the case of aluminum alloys, extensive work has already been carried out on precipitation and dissolution behavior using DSC from Keßler et al [3], in which methods for producing continuous cooling precipitation diagrams, as well as continuous heating dissolution diagrams, were developed. Measuring speed, and thus sample throughput, can be increased using non-equilibrium heating rates.…”
Section: Introductionmentioning
confidence: 99%